Multiple-twinning induced recrystallization and texture optimization in a differential-temperature-rolled AZ31B magnesium alloy with excellent ductility. Issue 5 (4th May 2022) - Peng, Ruizhi; Xu, Chun; Li, Yu; Zhong, Shaoxiong; Cao, Xiang; Ding, Yafei
Abstract : The effect of differential roller temperature (DTR) (low and high roller temperature difference: 60 and 180 K) on the microstructure evolution, deformation mechanism, and mechanical properties were investigated in a commercial AZ31B alloy sheet. Compared with the LDTR sample, a considerable shear strain ( 0.4) in the HDTR sample led to a multiple-twinning system, especially the formation of contraction twins (CTWs) and double twins (DTWs). After annealing, the HDTR-annealing (HDTR-A) sample achieved an excellent ductility (∼33.6%) as a result of a higher recrystallization fraction (∼71.75%) and more optimized texture component (max basal texture intensity decrease from 36.13–8.06). GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: A new method, differential temperature rolling, was used in AZ31B Mg alloy to induce multiple-twinning systems, which strongly influences the recrystallization mechanism and texture evolution, leading to a high ductility.